Interannual Variation in the Population Dynamics of Juveniles of the Deep-Sea Crab Chionoecetes tanneri - Chauvet, Pauline; Metaxas, Anna; Matabos, Marjolaine (Frontiers in Marine Science, 2019)
Understanding the population dynamics of commercially fished deep-sea species, on seasonal to inter-annual scales, is of great importance in areas where fishing pressure is high. The remoteness of the deep-sea environment constitutes a challenge for monitoring these populations. The few studies that have investigated population structure of deep-sea species, used trawls, a destructive approach for benthic ecosystems. The development of deep-sea observatories offers a continuous long-term presence on the seafloor. Using imagery from the Ocean Network Canada deep-sea observatory, video footage was acquired on a daily basis and analysed to describe the population dynamics of the deep-sea crab Chionoecetes tanneri located in depths of 900-1000 m in Barkley Canyon, off Vancouver Island (BC, Canada). The objectives here were to describe the dynamics of the local population in relation to changes in environment and/or life-cycle related behaviours. Sampling sites were located along the canyon axis and on the canyon wall. Only juveniles (1-10 cm) were found at the axis site (1000 m depth) with densities varying from 0 to 144 individuals/m2. On the canyon wall (900 m depth), adults (> 10 cm) were sporadically observed and densities were lower (max. 13 individuals/m2). Variations in density between the two sites reflected the observed arrival in summer and autumn of small individuals (< 2.4 cm) at the axis site. Apart from a distinct migration event in January 2015, intra-annual variability in density was higher than inter-annual variability as illustrated by significant annual and sub-annual cycles of 7.5 and 3.5 months. Our results confirmed the hypothesis of ontogenic migration and provides further insight into inter-molt periodicity; we demonstrated a duration of 16 months for one crab to grow from 1.8 cm to more than 5 cm. Our findings also show a correlation between population dynamics and chlorophyll concentration, surface wave height and wind speed, suggesting that surface blooms have a potential influence on the migration patterns of C. tanneri. Although our study was spatially limited (surface max 9 m), this innovative long-term study of a deep-sea crab demonstrates the potential of deep-sea observatories to enable research into the population dynamics of some deep-sea species.